FOXD3 Suppresses Tumor-Initiating Features in Lung Cancer via Transcriptional Repression of WDR5. (12th March 2019) - Xu, Wei; Li, Jialin; Li, Lei; Hou, Tianhui; Cai, Xiaopan; Liu, Tielong; Yang, Xinghai; Wei, Haifeng; Jiang, Cong; Xiao, Jianru
Abstract : The tumor-initiating cells (TICs) are a cell population that can initiate tumor occurrence, mediate drug resistance, and give rise to metastasis. FOXD3 is a forkhead box (Fox) transcription factor family that regulates the pluripotency of embryonic stem cell and tumorigenicity. However, it is unclear whether FOXD3 plays any role in TIC and tumor metastasis. The functional analysis of FOXD3 was performed by oncospheres formation and redifferentiation, drug resistance assay, and cell migration. Global genomic RNA-Seq and ChIP-Seq analysis were used to identify the direct target of FOXD3 in lung cancer. We demonstrated that downregulation of FOXD3 in TICs was positively correlated with higher histologic grades and positive lymph node metastasis. FOXD3 repressed TIC expansion and cell migration, drug resistance, and osteoclasts in vitro and in vivo. Mechanically, we found that FOXD3 represses WDR5, which regulates TIC-related signaling pathway. Moreover, WDR5 were positively correlated with the TIC abundance and tumor progression. Besides, patients with high expression of WDR5 presented a poorer overall survival. FOXD3 may suppress TIC accumulation by repressing the expression of WDR5 in lung cancer. Stem Cells   2019;37:582–592 : Abstract : FOXD3 suppresses the expansion of tumor-initiating cells. In the tumor initiating cells, the expression of FOXD3 is low, which releases the suppression effect on WDR5 expression level and promotes the self-renewal and chemoresistance of tumor-initiating cells, thus contributing to the metastasis of lung cancer.